International Monetary Fund annual report: 1998 - International Monetary Fund (Washington DC, 1998)
The Annual Report to the Board of Governors reviews the IMF's activities, policies, and liquidity position during the financial year (May 1, 1997 through April 30, 1998), as well as developments in the world economy, including balance of payments problems of its member countries, exchange rates, international and emerging capital markets, fiscal considerations in policy making, data issues, and the debt situation.
osc 8/09/2021
Ref
Keywords: International Monetary Fund; Annual Report